Spatial Distribution Of Chlorofil-a In Laguna Kabori Manokwari Regency - Suci Widya Warnetti; Thomas Frans Pattiasina; Fitriyah Irmawati Elyas Saleh; Alianto Alianto; Selfanie Talakua; Marthin Matulessy (Faculty of Agriculture Musamus University, 2020)
Kabori Lagoon is a lagoon located in Manokwari Regency, West Papua, where the water quality data is still very limited. Chlorophyll-a is the most important photosynthetic pigment for aquatic plants such as phytoplankton. The purpose of this study was to determine the horizontal distribution of chlorophyll-a based on the spatial data approach in the waters of the Kabori Lagoon. The study was conducted from April to May 2019. The sampling point was determined by purposive sampling at eight points for sampling of chlorophyll-a and water parameters including physics and chemistry (temperature, DO, salinity, brightness and depth). Measurement of physical and chemical parameters is carried out in situ. Chlorophyll-a analysis was carried out at the Laboratory of Water Productivity and Quality, Faculty of Marine and Fisheries Sciences, Hasanuddin University. Spatial data processing used ArcGIS 10.4 and Surfer 16 to create chlorophyll-a distribution maps and bathymetry. The results showed that the chlorophyll-a content in Observation I was in the range of 0.12-2.40 mg/m3 and in Observation II it was in the range of 1.43-10.84 mg/m3. Based on the chlorophyll-a content, the Kabori Lagoon is included in the mesotrophic category. Spatially, the distribution of chlorophyll-a content varies, but tends to be higher in the southern part of the lagoon than in the northern part of the lagoon. Spatial distribution, Chlorophyll-A, Kabori Lagoon, Mesotrophic